2014
DOI: 10.1007/s10896-014-9653-y
|View full text |Cite
|
Sign up to set email alerts
|

Security in Father-child Relationship and Behavior Problems in Sexually Abused Children

Abstract: While the influence of mother-child relationships on children's recovery following sexual abuse has been documented, less is known about the possible contribution of father-child relationships on outcomes. The present study explored the contribution of children's perception of security in their relationship to the father on internalizing and externalizing behavior problems, while controlling for sociodemographic variables and variables associated with the mother-child relationship. Participants were 142 childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 54 publications
0
12
0
1
Order By: Relevance
“…Likewise, recent studies show that negative family interactions between parent and child are associated with higher levels of anxiety and depression [23,[38][39][40], whereas communication between the parents and the child may be influenced by several factors, such as a divorce of the parents [41,42]. Moreover, recent studies exploring father-child relationships have proposed an "activation relationship", where fathers also tend to encourage children to take risks, while at the same time ensuring their safety and security [43][44][45][46][47]. Family communication plays an important role in the occurrence of EBP in adolescence [41].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, recent studies show that negative family interactions between parent and child are associated with higher levels of anxiety and depression [23,[38][39][40], whereas communication between the parents and the child may be influenced by several factors, such as a divorce of the parents [41,42]. Moreover, recent studies exploring father-child relationships have proposed an "activation relationship", where fathers also tend to encourage children to take risks, while at the same time ensuring their safety and security [43][44][45][46][47]. Family communication plays an important role in the occurrence of EBP in adolescence [41].…”
Section: Discussionmentioning
confidence: 99%
“…Research on attachment theory has focused predominantly on the mother–child relationship (Bretherton, 2010; George & Solomon, 2008; Palm, 2014; Parent-Boursier & Hebert, 2015).…”
Section: Attachment Theory: the Road To Considering The Role Of Fathersmentioning
confidence: 99%
“…When considering the various factors in a child’s life that build resilience, the responses and reactions of caregivers matter. In both theory and practice, a child’s caregivers have often been named as the most vital and influential supports in child development (Andersson, 2005; Bolen & Lamb, 2007; Grossmann, Grossmann, Kindler, & Zimmermann, 2008; Harden, 2004; Parent-Boursier & Hebert, 2015; van der Kolk, 2003). Yet the term “caregiver” has changed over time.…”
mentioning
confidence: 99%
“…In this respect, the presence of a healthy communication between fathers and their children is important for the development and positive behaviours of children. The studies have also suggested that fathers are very important for their children (Amato, 1994;Benzies, and Evans, 2015;Bowey, 1995;Culpin et al, 2013;Downer and Mendez, 2005;Ferreira et al, 2016;Kochanska et al, 2015;Parent-Boursier and Hébert, 2015). For instance, in the study conducted by Levesque (2009) to investigate the father figure in preschool children, it was determined that four-year-old male children displayed behaviours reflecting the figure of father in their symbolic games at least once.…”
Section: Introductionmentioning
confidence: 99%